Evidências de validação empírica de escala de atitude empreendedora e testagem de um modelo preditivo a partir dos Cinco Grandes fatores de personalidade - Cortez, Pedro Afonso (2017)
Entrepreneurship has become atopic of interest in different areas of study. There are many concepts and theoretical approaches presenting conceptual overlap. Among the various objects of study related to the phenomenon, the present investigation has deepened in the concept of Entrepreneurial Attitude (AE), which based on a consistent theoretical basis when compared to other concepts of the area. The main objective of the present research was analyze the evidences of empirical validation and culturally adapt an AE for the Brazilian context (study one) and test a predictive model of the AE through the Big Five personality factors, individual and academic experiences (study two). The second study also had as specific objectives the confirmatory analysis of empirical validation evidences from AE, Big Five and entrepreneurial intention scales. The entrepreneurial intention measure was apply to evaluate the discriminant validity of the constructs. The sample selected by convenience consisted of 638 major degree university students from a federal public institution of psychology, physical education, biomedical engineering, administration, law, medicine, pedagogy, nursing, nutrition and accounting sciences with a mean age of 21 years (SD = 2.2). The application of the instruments was collective in the classroom using pencil and paper. The participants were randomly assigned into two groups with similar characteristics. It had implied in n= 322 for the first study and n= 316 for the second study. The results of first study shown adequacy of the adaptation of AE measure to the Brazilian reality and the exploratory factorial analysis indicated satisfactory psychometrics evidences. The final measurement of AE was composed by the factors leadership, creativity, achievement and risks, its reliability covered from 0.74 to 0.62. In the second study, we carried out the confirmatory factorial analysis of AE, Big Five (conscientiousness, neuroticism, openness, agreeableness and extraversion) and entrepreneurial intention. The adjustment indicators for the measurement models were considered reasonable and adequate. The composite reliability of the AE varied between 0.64 and 0.75, for Big Five the oscillation was between 0.69 and 0.90 and for the scale of entrepreneurial intention was 0.97. Discriminant validity was proofed, since all factors of AE and Big Five personality had adequate indexes (VEM> r2) when contrasted with the entrepreneurial intention, showing difference between the constructs and factors analyzed. To test the predictive power of AE through Big Five, personal and academic experiences (scientific initiation, extension university programs, internship, class monitor, entrepreneurial activities, and family business) three predictive models were specified, the first one related to the personality traits, the second related to personal and academic experiences, which resulted in the proposition of the final integrated model between experiences and personality factors. The final model presented excellent adjustment indices (X2 (37) = 41.425; X2 / df = 1.120; CFI =, 986; PCFI = 663; GFI = 0.974; PGFI = 546; RMSEA =.021; MECVI =,383), when compared to the initial proposals, explaining 6% of the AE risk through a unique contribution of the openness ((3 = 0.13 p <0.01) and entrepreneurial activities ((3 = 0.18 p <0,01); 21 % of explanation to the AE leadership through the extraversion ((3 = 0.27 p <0.01) and conscientiousness ((3 = 0.25 p <0.01); 24% of the creativity through the significant contribution of the conscientiousness ((3 = 0.48 p <0.05) and neuroticism ((3 = -0.10 p <0.05). There was no predictive trajectory for the achievement factor. When considering Big Five y as antecedent of an AE, the findings are consonant with the literature, all dimensions, except agreeableness, predicted AE, being positive related for conscientiousness, openness, extroversion and negative for neuroticism. Considering academic experiences as predictors, it shown that extension university programs and entrepreneurial activities have proved to be positive and significant predictors. Finally, we expect that the study may contribute in strategies to evaluate the personal characteristics of entrepreneurs and promote entrepreneurship in the national reality.